2017
DOI: 10.1007/s11356-017-9007-4
|View full text |Cite
|
Sign up to set email alerts
|

Distance-dependent varieties of microbial community structure and metabolic functions in the rhizosphere of Sedum alfredii Hance during phytoextraction of a cadmium-contaminated soil

Abstract: The recovery of microbial community and activities is crucial to the remediation of contaminated soils. Distance-dependent variations of microbial community composition and metabolic characteristics in the rhizospheric soil of hyperaccumulator during phytoextraction are poorly understood. A 12-month phytoextraction experiment with Sedum alfredii in a Cd-contaminated soil was conducted. A pre-stratified rhizobox was used for separating sub-layer rhizospheric (0-2, 2-4, 4-6, 6-8, 8-10 mm from the root mat)/bulk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 102 publications
2
8
0
Order By: Relevance
“…However, the trends were complex when compared with unplanted soil. These were consistent with previous studies' indications that microbial biomass clearly increased in rhizospheric soils compared to bulk soil [16,[62][63][64]. Similarly, T. caerulescens growth increased microbial respiration rates in the Zn-and Cd-contaminated soil [23].…”
Section: Effects Of S Integra Planting and Pb Pollution On Soil Propsupporting
confidence: 92%
See 3 more Smart Citations
“…However, the trends were complex when compared with unplanted soil. These were consistent with previous studies' indications that microbial biomass clearly increased in rhizospheric soils compared to bulk soil [16,[62][63][64]. Similarly, T. caerulescens growth increased microbial respiration rates in the Zn-and Cd-contaminated soil [23].…”
Section: Effects Of S Integra Planting and Pb Pollution On Soil Propsupporting
confidence: 92%
“…The difference between bulk soil and unplanted soil seen with S. integra planting not only had direct effects on rhizospheric soil, but also had indirect effects on bulk soil. As in the earlier studies, the effects of the rhizosphere should not be limited to specific volumes [62,67]. For instance, the rhizosphere effects of Sedum alfredii on the microbial community structure and metabolic function were not limited to the root surface, notwithstanding that the effect decreased as the distances increased [62].…”
Section: Effects Of S Integra Planting and Pb Pollution On Soil Propmentioning
confidence: 72%
See 2 more Smart Citations
“…A high-throughput sequencing approach was therefore used to measure rhizospheric bacterial community that may influence the accumulation of heavy metal in S. integra. Planting S. integra decreased the total Pb concentration both in rhizosphere and bulk soil in the low Pb treatment, which could be explained by the effects of root activity not being limited to the root surface, though the effect declined when the distances increase (Yang et al, 2017). Furthermore, our previous study also showed that microbial quantity and metabolism were promoted both in the rhizosphere and bulk soil in the low Pb treatment (Niu et al, 2019).…”
Section: Discussionmentioning
confidence: 78%